Beyond The Medical And Popular Gaze: Writing The Wounds In Kiera Van Gelder’s Memoir, The Buddha And The Borderline (Journal of Pharmaceutical Negative Results, 2023)
This paper addresses exclusively the role of language in the projection of self and construction of identity of individuals who suffer from mental health issues. The language generated through psychiatric diagnoses is extremely reductionist and intertwined with the rhetoric of normalcy. It distorts the understanding of mental health issues in the population’s consciousness by utterly negating the self and personhood of sufferers, and it follows a pattern of stigmatisation, devaluation and exclusion. In opposition, Kiera Van Gelder’s memoir of suffering and recovery from borderline personality disorder, The Buddha and the Borderline, is an act of resistance that debunks the clinical gaze and provides a counter diagnostic narrative depicting the diverse emotional and existential realities of a sufferer’s embodiments. Kiera’s narrative in a first-person language shatters the very question of objectivity and subjectivity of truth raised in the context of autobiographical works based on mental health issues and accommodates all considerable incoherencies and inconsistencies temporally and spatially. Her memoir is not merely an act of writing rather it is a courageous act of collapsing the closet, holding the subject position and vocalising the voice of the other.